Effect of a Proposed Educational Program for Popular Games on the Development of Cognitive-Motor Abilities and Deductive Thinking Among Primary School Students in Nineveh Governorate - Basem, Jamal Shukry; Najm, Mohammed Suhail (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2026)
This study aimed to investigate the impact of an educational program based on traditional popular games on the development of cognitive-motor skills and deductive reasoning among primary school students in Nineveh Governorate. The research population consisted of fourth-grade students at Al-Hadhara School for Boys during the 2024–2025 academic year. A random sample of 80 students was selected, with Class C as the experimental group and Class D as the control group. Both groups were statistically equivalent and homogeneous across key variables to ensure experimental validity. The study employed an experimental method using an equivalent-groups design with pre- and post-testing over an eight-week intervention. The educational program included various traditional games, exercises, and activities derived from local popular games. The findings indicated that the program significantly enhanced the cognitive-motor skills and deductive reasoning of students in the experimental group, while the control group following the traditional curriculum showed no significant improvement. These results suggest that structured programs incorporating culturally relevant popular games can effectively promote both motor and cognitive development in primary school children.